The impact of widowhood on the mental health of older adults and the buffering effect of social capital - Zheng, Jichao; Yan, Lei (Frontiers in Public Health, 2024)
Background: Widowhood is one of the most serious issues affecting the mental health of older persons. China currently has tens of millions of widowed elderly, which is a huge group. It is of great significance to study the impacts of widowhood on their mental health and put forward some measures for improvement. Method: We used China Family Panel Studies (CFPS) data in 2020, which included 4,184 older adults. Linear regression is used to examine the relationship among widowhood, mental health, and social capital. Results: Both short-term and medium-and long-term widowhood lead to a significant increase in depression, which seriously affects the mental health of older people. At the same time, community-level and family-level social capital have significant buffering effects on the loss of mental health caused by widowhood, but this effect is heterogeneous, with different types of social capital playing different roles among different gender groups.The provision of care support by children and good neighborhood relationships can help mitigate the psychological impact of widowhood, and these are areas where social policy can make a difference